1998
DOI: 10.2737/pnw-gtr-421
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wind disturbance on temperate rain forest structure and dynamics of southeast Alaska.

Abstract: Nowacki, Gregory J.; Kramer, Marc G. 1998. The effects of wind disturbance on temperate rain forest structure and dynamics of southeast Alaska. Gen. Tech. Rep. PNW-GTR-421. Portland, OR: U.S. Department of Agriculture, Forest Service, Pacific Northwest Research Station. 25 p. (Shaw, Charles G., III, tech. coord.; Julin, Kent R., ed.; Conservation and resource assessments for the Tongass land management plan revision).Wind disturbance plays a fundamental role in shaping forest dynamics in southeast Alaska. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 43 publications
2
71
0
Order By: Relevance
“…In contrast, we assume that most old-growth forests and wetlands/peatlands on the 13,000-and 50,000-year-old surfaces have a lifespan of hundreds to thousands of years. These old landscapes will also support many of the early-seral associations as a minor part of the landscape because disturbances initiating primary succession do occur such as mass wasting and avalanches (Nowacki andKramer, 1998, Snyder et al, 2008). These results highlight the importance of not only the older landscapes for conserving ecosystem diversity, but also that of newly deglaciated surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we assume that most old-growth forests and wetlands/peatlands on the 13,000-and 50,000-year-old surfaces have a lifespan of hundreds to thousands of years. These old landscapes will also support many of the early-seral associations as a minor part of the landscape because disturbances initiating primary succession do occur such as mass wasting and avalanches (Nowacki andKramer, 1998, Snyder et al, 2008). These results highlight the importance of not only the older landscapes for conserving ecosystem diversity, but also that of newly deglaciated surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, she observed that only 24% of the trees that died had uprooted whereas 52% had broken and 23% had died standing. According to Nowacki and Kramer (1998), tree snapping would dominate in small gaps whereas uprooting would be more prevalent in larger gaps. Hence, our gap size is consistent with a gap created by a strong wind uprooting the trees.…”
Section: Experimental Windthrowmentioning
confidence: 99%
“…Windstorms are a major disturbance force that shapes the age, structure, and function of forests in this region (Nowacki and Kramer 1998). Widespread, stand-replacing events occur at 100-year intervals, with exposure to the prevailing southeast storms increasing the likelihood of catastrophic wind disturbance.…”
Section: Types Of Change In Alaskan Forestsmentioning
confidence: 99%